120 Safety and efficacy of renal artery denervation for uncontrolled-resistant hypertension in a high risk population with CKD: the Verona real-world experience. (8th December 2021) - Fezzi, Simone; Castaldi, Gianluca; Widmann, Maddalena; Marin, Federico; Ruzzarin, Alessandro; Tavella, Domenico; Ribichini, Flavio
Abstract: Aims: To evaluate the safety and the efficacy of catheter-based radiofrequency renal sympathetic denervation (RSD) in a daily practice population of patients with uncontrolled resistant hypertension on top of medical therapy. Methods and results: Consecutive unselected patients with uncontrolled resistant hypertension undergoing RSD were enrolled. Office and ambulatory blood pressure (BP) monitoring were collected at baseline and 3, 6, and 12 months after RSD. Efficacy was assessed also in patients with an estimated glomerular filtration rate below 45 ml/min/1.73 m 2 . Patients were defined responders to RSD if systolic BP decreased by at least 5 mmHg at ambulatory BP or by 10 mmHg at office BP at the last follow-up available. Fifty-four patients with multiple comorbidities underwent RSD for uncontrolled-resistant hypertension from 2012 to 2021. Baseline office and ambulatory BP was 161.0/87.2 ± 24.1/15.6 mmHg and 155.4/87.5 ± 19.3/14.6 mmHg, respectively. At 12-month follow-up a significant reduction of office and ambulatory systolic BP, respectively by − 15.66 ± 29.73 mmHg ( P  < 0.01) and by − 11.3 ± 23.1 mmHg ( P  < 0.05), was noticed. BP reduction at 12-month follow-up among patients with eGFR <45 ml/min was similar to that obtained in patients with higher eGFR. Among patients treated before July 2020 with available follow-up (45/54) 36 patients (80%) were classified as responders. Combined hypertension, higher ambulatory systolic BP and lower E/E' at baseline emerged as predictors of success of RSD at univariate analysis. Among responders and non-responders, the average medication number showed no significant difference at baseline and during follow-up. No major complications were observed and renal function was stable up to 12 months, even in patients with lowest eGFR at baseline. Conclusions: RSD is safe and feasible in patients with uncontrolled resistant hypertension on top of medical therapy, even in a high-risk CKD population with multiple comorbidities, with a significant reduction of systolic BP and a trend of reduction of the diastolic BP up to 12 months.